Determination of the position vectors of curves from intrinsic equations in G3 - Öztekin, Handan; Tatlipinar, Serpil (Walailak University, 2014)
In this paper, we investigate the position vectors of the curves and the general helices in Galilean space G3. We find the differential equations for the position vectors of such curves. © 2014 Walailak University. All rights Reserved.
Keywords: Galilean space; Helix; Position vector